Complexity of innovative financial products: The case of synthetic exchange traded funds in Europe - Marszk, Adam (Złożoność innowacyjnych produktów finansowych: przypadek syntetycznych exchange traded funds w Europie, 2016)
The aim of the text is the presentation of the most important categories of exchange traded funds (ETFs) – physical and synthetic ones. A theoretical part of the text includes an overview of the main features of ETFs, the presentation of the differences between physical and synthetic funds and the main risks posed by both types to their users and the whole financial systems. An empirical part focuses on the European market. The time span of the analysis covers the years 2001-2015 (or shorter periods in cases of lack of sufficient data). Using key statistics regarding the European ETFs market, its size, structure (both historically and currently) as well as predictions of the main future changes are discussed. The main results of the research indicate that the size of the European ETFs market, both in terms of the assets under management and number of listed funds, has been growing in recent years, yet at a rate lower than before the global financial crisis. An important observed change on the European ETFs market is the declining share of synthetic ETFs after their peak popularity in 2010. The most recent data from the first months of 2015 confirm this trend. Considering the data on cash flows into these two categories, physical ETFs will most probably continue to increase their market share compared to synthetic ones
Nauki o Finansach = Financial Sciences, 2016, Nr 2 (27), s. 49-64
Keywords: exchange traded funds; financial innovation; mutual funds; financial markets; innowacje finansowe; fundusze inwestycyjne; rynki finansowe